A presença do ensino do léxico na formação continuada do professor da educação básica no Paraná. - Jacoby, Mariana Fonseca Ferreira (2025)
The main theme of this research is the teaching of the lexicon in online courses designed for the continuing education of English language teachers working in basic education in state schools in Paraná. We can see that continuing education plays a fundamental role in teaching. By keeping their practice and fluency in the foreign language they teach up to date, as well as their didactic-pedagogical knowledge, teachers become better prepared to understand and meet the needs of their students, through adapted practices and more intentional teaching. In addition, continuing training aims to promote recognition and appreciation of the teachers in question (NÓVOA, 1997), or at least that is what is expected. In case of the state of Paraná, as we will see below, training is offered, but its recognition is negligible. From a general perspective, few studies on teaching the lexicon have addressed the issue of continuing education, in a way that also encompasses continuing education offered through online courses, especially those selected to make up the corpus of our research. Thus, the general objective is to identify how the lexicon is approached in the courses: Language Improvement for Teachers (LIFT), Learn English and EnglishCentral, through the Program Inglês Professor, which is compulsory for English teachers in the state of Paraná. Thus, we seek to answer the following guiding question that mobilizes this research: how has the lexicon been taught to English language teachers through the digital educational tools presented as possibilities for in-service training in Basic Education in Paraná? In order to answer these questions, we will use as a basis some guiding documents, such as the National Education Guidelines and Bases Law (LDB) (BRASIL, 1996) and the National Curriculum Guidelines (DCNs) for Basic Education Teacher Training (BRASIL, 2001). In addition to studies that conceptualize continuing education Nóvoa (1991), Candau (1996), Palma Filho and Alves (2003) and Almeida Filho (2014); digital competence in education Behar and Silva (2019; 2022) and the use of digital tools in teacher training Unesco (2006; 2021) and the European Commission (2012). As for studies of the lexicon and contributions from Lexicology, Biderman (1992; 1996; 1998; 1999; 2001a; 2001b) and Barbosa (1992; 1997), followed by highly relevant readings on teaching the lexicon and lexical competence by Nation (1990; 1997; 2001; 2005), Leffa (2000; 2016), Nadin (2015) and Gil (2016), provided us with subsidies for analyzing the corpus of this research, which was carried out using basic level activities present in the three online courses selected. In general, the results show a great deal of recurrence within the three lexical teaching strategies selected as the basis of the analysis: lexical fields, translation and equivalents and multimodality with a focus on the use of images, however, the results have not yet been sufficient.